2012
DOI: 10.1108/01437721211243778
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and retirement age intentions in Finland

Abstract: Purpose -The purpose of this paper is to analyse the effect of job satisfaction on the intended retirement age of self-employed and organisationally-employed white-collar professionals. The analysis also examines potential boundary conditions imposed by other domains of life for the applicability of this relationship. Design/methodology/approach -The study employs ordered probit regressions to analyse primary survey data comprising 1,262 Finnish white-collar professionals. Findings -The econometric results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
1
23
0
2
Order By: Relevance
“…This is in agreement with results from earlier research covering a wide spectrum of occupations (e.g., Buyens et al 2009;Kautonen et al 2012;Sibbald et al 2003). For instance, in a study of retirement intentions among employees of a large public employer, Oakman and Wells (2013) found that of work factors that were analyzed, low job satisfaction indicated an increased likelihood of retiring soon.…”
Section: Effect Of Work Satisfactionsupporting
confidence: 91%
“…This is in agreement with results from earlier research covering a wide spectrum of occupations (e.g., Buyens et al 2009;Kautonen et al 2012;Sibbald et al 2003). For instance, in a study of retirement intentions among employees of a large public employer, Oakman and Wells (2013) found that of work factors that were analyzed, low job satisfaction indicated an increased likelihood of retiring soon.…”
Section: Effect Of Work Satisfactionsupporting
confidence: 91%
“…Apesar de parte da amostra ter assinalado que a aposentadoria foi voluntária, 64% afirmaram que, se pudessem, voltariam a trabalhar. Os participantes que descreveram a satisfação no trabalho como ótima, com maior frequência do que os demais, disseram terem aposentado de forma involuntária, por motivos externos, indicando que quanto maior a satisfação com a carreira, menor a voluntariedade para se aposentar, o que vem ao encontro de estudos anteriores que apontam a satisfação no trabalho como um importante determinante da intenção de prolongar a carreira (Kautonen et al, 2012). Para Fontoura et al (2015), as pessoas que tendem a adotar uma postura de realizar muitas atividades de busca de valor instrumental para o período pós-aposentadoria são geralmente as que, em seu percurso laboral, conferiam centralidade ao trabalho.…”
Section: Discussionunclassified
“…Estudos sobre os antecedentes da decisão para o bridge employment têm demonstrado que, além da saúde e dos atributos financeiros (Bonsang & Klein, 2012), variáveis psicológicas relacionadas com o trabalho, como as atitudes de emprego, estressores da função de trabalho (Pengcharoen & Shultz, 2010;Wang et. al., 2008) e satisfação com o trabalho (Kautonen, Hytti, Bögenhold, & Heinonen, 2012) são fortes preditores da decisão de aposentadoria. Outras pesquisas revelam que participar de bridge employment pode ser benéfico para a saúde física e mental e para a satisfação de vida (Dingemans & Henkens, 2014) dos aposentados.…”
unclassified
“…In addition to financial influences, work related factors are also important determinants of retirement intentions (Fisher, Chaffee, & Sonnega, 2016;Heponiemi et al, 2008;Schmidt & Lee, 2008. Job satisfaction, "a positive (or negative) evaluative judgement one makes about one's job situation" (Weiss, 2002, p. 175) has emerged as a key determinant of retirement intentions and retirement (Bidewell, Griffin, & Hesketh, 2006;Kautonen, Hytti, Bögenhold, & Heinonen, 2012). Past studies have shown low job satisfaction pushed workers towards early retirement (Fisher et al, 2016;Shultz et al, 1998; whereas, workers with high job satisfaction were pulled towards work and retired later (Fisher et al, 2016;Steger & Dik, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%